PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI BUDIDAYA LEBAH TRIGONA PENGHASIL MADU DI DESA SUDIMORO KECAMATAN TULUNG KABUPATEN KLATEN (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2022)
: Sudimoro Village is one of the villages in Klaten Regency. Most of the residents of Sudimoro Village are engaged in agriculture. Meanwhile, Sudimoro Village has the potential for natural tourism that can be a source of food for Trigona honey bees. Trigona honey bee cultivation is expected to be able to empower the community's economy so that the surrounding community has economic resources other than agriculture. Trigona honey bee cultivation is expected to produce honey that can be a product of Sudimoro Village to support the One Village One Product Program. In addition, it is expected to be able to attract tourists to visit Sudimoro Village. The implementation method used in this activity is counseling, lectures, question and answer discussions, then continued with mentoring training. The target partners in this Community Service activity are the Sudimoro Village Community, the Kalimosodo Tourism Object Management, and PKK women. The results achieved from this service activity are that the target partners are able to cultivate trigona honey-producing bees, starting from breeding to producing honey.